The Influence of Leadership, Organizational Culture and Motivation on Employee Performance in the Regional Representative Council of Lahat District - , Aliman Syahri; Helmi, Sulaiman; Herdiansyah , M. Izman; Trisninawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the current era of globalization, competition between organizations is becoming increasingly high so that every organization is required to always be ready to face changes that will occur and improve related matters so that they can continue to survive and develop. The method in this research uses a quantitative type of research in measuring the strength between independent variables and dependent variables in a population. Quantitative methods are a form of research that is based on systematically collecting data about the subject under study to combine related variables. Based on the analysis above, several conclusions can be drawn based on the research results, it is known that organizational culture has a positive and significant influence on employee performance. Leadership does not have a significant influence on performance. Motivation has a positive and significant influence on employee performance. And the influence of organizational culture, leadership and motivation has a positive and significant influence on employee performance